Making and shaping things in creative economies - Jerlei, Triin (Vilnius University Proceedings, 2019)
Abstract book for symposium “Making and shaping things in creative economies. From history to present day” organised by Vilnius University, 28-30 November 2019. This symposium studies the ways design is organised and managed with different political processes and policies, both in past and present. Instead of focusing solely on the content of policies, politics and management, it attempts to create a wider debate within the framework of culture, creativity and economy. The event looks at the impact that the specific policies and individuals, organisations or institutions behind them have on existing design culture. In addition to the act of designing, the possible subjects include policies shaping all stages in the life cycle of an object, for example promotion, consumption, collecting objects or recycling them, as well as positioning design in a wider political context. Within the international symposium “Making and shaping things in creative economies” an event is dedicated to the study of art and culture within local creative economies and industries in Lithuania and nearby. The aim is to research the ways art is managed and organised with different strategies, processes and policies. Instead of focusing solely on the content of policies, politics and management, it creates a wider debate within the framework of culture, creativity and economy.
Keywords: design; design history; creative industries